A comparative study of the compressive behaviour of AISI 321 austenitic stainless steel under quasi-static and dynamic shock loading. (15th December 2016) - Tiamiyu, A.A.; Eskandari, M.; Nezakat, Majid; Wang, Xu; Szpunar, J.A.; Odeshi, A.G.
Abstract: The mechanical response of AISI 321 austenitic stainless steel under both dynamic and quasi-static compression was studied and compared. Compression in both loading conditions led to strain-induced phase transformation which follows the FCC ɣ-austenite → BCC ά-martensite sequence. During deformation in both loading conditions, precipitation of nano-sized carbide and evolution of strain-induced martensite contributed to strengthening while plastic deformation mechanisms occurred in the specimens by slip and mechanical twinning mechanisms. Specimens subjected to quasi-static compression exhibited lower yield strength and higher strain hardening capacity than the dynamically impacted specimen. While deformed shear band (DSB) characterized by elongated grains developed in the quasi-statically compressed specimen, transformed shear band (TSB) characterized by nano-grains (average size of 0.28 μm) were formed in the dynamically impacted specimen. The texture of the FCC austenite in all regions of the specimen under both loading conditions is predominantly 〈110〉 || CD (compression direction) with minor 〈111〉 || CD component. Large strain localization in the TSB of an impacted specimen led to off-〈110〉 || CD texture in the FCC austenite. In BCC martensite, 〈111〉 || CD and 〈100〉 || CD fibres are the predominant texture components in specimens subjected to dynamic impact and quasi-static loading, respectively. Graphical abstract: Highlights: Mechanical response of AISI 321 austenitic stainless steel under both dynamic and quasi-static compression was studied. Lower yield strength and higher strain hardening capacity were observed under quasi-static loading. Precipitation of nano-sized carbide and formation of strain-induced martensite contributed to strengthening. TSB in impacted specimens consist of ultra-fine grain structure which form by rotational dynamic recrystallization. Large strain localization inside the TSB in an impacted specimen leads to off-〈110〉 || CD texture in austenite phase.